A Comparative Study on Damage Variable and Geo-Mechanical Properties of the Pre-Damaged Rock Specimen - Lei Wen; Yang Huang; Jia-xin Wen; Xin Zhang; Wen-qiang Lu (Advances in Civil Engineering)
The initial damage of a rock mass plays an essential role in parameter evaluation of that rock mass. How to determine the initial damage of a rock mass is therefore a problem that must be solved. To study the mechanical properties of a rock mass, pre-damaged specimens with different degrees of damage are prepared using uniaxial compression. The degree of damage of the pre-damaged specimens is determined by using their physical and mechanical parameters; that is, four methods are used to calculate the damage variables. Comparing the calculated damage variables using the four methods, we find the following: (1) the damage variables of different calculation methods are quite different. (2) When the degree of damage is slight, in other words, the micro-cracks are in the initial state of growth, and the calculated damage variables have little difference when using various methods. (3) When the degree of damage is severe, that is, the micro-cracks coalesce to form macro-cracks, the calculated damage variables significantly deviate when using various methods. Only the calculated damage variables using the BTS are larger than those calculated using other methods, mainly because there is almost no friction effect of cracks in BTS testing. Finally, to verify the accuracy and feasibility of the damage variables of various calculation methods, the uniaxial compressive peak strength of the pre-damaged specimens is determined by using the effective strain hypothesis and the damage variable. The 1 : 1 slope line is used to verify the deviation between the measured values and calculated values.